Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Lembaga Perkreditan Desa (LPD) Desa Adat Ngis - Gede Adi Yuniarta; tiaswari, Ni Made Tia Swari (Vokasi : Jurnal Riset Akuntansi, 2022)
This study aims to assess the financial performance of the Ngis Traditional Village LPD in 2018-2021. This research is quantitative research. The data used is secondary data, the data collection technique is done by the documentation method. The object of this research is the analysis of financial ratios to assess financial performance. The data used in this study is the financial report of the Ngis Traditional Village LPD in 2018-2021. The data analysis technique used is quantitative descriptive analysis. The results of the study show that the current ratio of the Ngis Traditional Village LPD for the last 4 years illustrates that the financial performance position of the Ngis Traditional Village LPD is in an unfavorable position. The results of the debt to asset ratio for the last 4 years illustrate that the financial performance position of the Ngis Traditional Village LPD is in very poor criteria. The net profit margin of the Ngis Traditional Village LPD for the last 4 years is in very good criteria. The results of the total assets turn over for the last 4 years of the Ngis Traditional Village LPD are in very poor criteria.